SAT0150 Soluble FAS/FASL levels in rheumatoid arthritis patients treated with infliximab and adalimumab. (23rd January 2014) - Terenzi, R.; Guiducci, S.; Nacci, F.; Romano, E.; Manetti, M.; Peruzzi, F.; Bruni, C.; Bartoli, F.; Matucci-Cerinic, M.
Abstract : Background: Rheumatoid Arthritis (RA) is an autoimmune disease characterised by chronic inflammation and synovial hyperplasia caused by influx of inflammatory cells and by a reduced rate of programmed cell death. In RA synoviocytes seem to be resistant against apoptosis and not sensitive to TNF-induced apoptosis; by contrast, TNF induces them to proliferate. In this contest TNF- α strongly interfere with Fas (CD95)–Fas ligand (FasL, CD178) death receptor pathway. Biological drugs seem to be able to induce synovial apoptosis by inhibiting TNF-α functions. With the present study we want to investigate possible links between serum sFas and sFasL and anti-TNF therapy. Objectives: to investigate whether sFas and sFasL serum levels can be associated to therapeutic response to TNF antagonists (anti-TNF) Infliximab and Adalimumab in patients with RA; to correlate these values with disease activity variables. Methods: circulating levels of sFas and sFasL were investigated by specific immunosorbent assay on serum samples (52 RA patients: 36 female, 16 male; mean age: 45.7±12.2 years). The variables of disease activity (analyzed by DAS28, HAQ, CRP), physical function and sFas/sFasL serum levels were determined before and after 3 months of anti-TNF therapy (32 Adalimumab and 20 Infliximab). All patients were naïve to anti-TNF therapy. 40 (28 female, 12 male) age- and sex-matched healthy controls were used as controls. The sFas/sFasL levels are expressed as means ± standard deviations (SD) and compared by Student's t-test and Mann-Whitney Test. Spearman rank correlation test (Rs) were employed to examine relationships between serum levels and disease activity variables (analyzed by DAS28, CRP). The differences are considered significant for p values <0.05. Results: disease activity of patients was severe (baseline DAS28 5.6±1, HAQ of 3.5 (2.3 to 4.1 interquartile range) CRP 12 mg/l (IQR: 9 to 16). Before anti-TNF therapies sFas and sFasL levels were not different between RA patients and controls (5278.44±271.1 vs 5869.09±256.1 pg/ml for sFas; 56.72±20.32 vs 48.74±12.22 pg/ml for sFasL). After 3 months of Infliximab and Adalimumab therapy, RA patients showed higher concentration of serum sFas (9343.61±2356.6 p<0.01 for Infliximab; 7281±1123.3 p<0.05 for Adalimumab). Clinical response correlated with serum sFas levels after 3 months of anti-TNF treatment (Infliximab/DAS28: Rs= -0, 681; Infliximab/PCR: Rs= -0, 643; Adalimumab/DAS28: Rs= -0, 743; Adalimumab/PCR: Rs= -0, 746) as demonstrated by significantly reduction of CRP (0, 6 mg/l; IQR 0, 3 to 2, 8) and DAS28 (2, 8±0, 5) (p<0, 05). No differences were about serum sFasL levels before starting biological treatment and after 3 months of therapies (50.53±33.3 for Infliximab; 51.47±43.5 for Adalimumab). Conclusions: after Infliximab and Adalimumab therapy RA patients showed higher serum levels of sFas, but no sFasL. This results also correlate with variables of disease activity. This may suggest that Infliximab and Adalimumab blocking TNF-α functions are able to reduce disease activity at least in part by promoting synovial apoptosis, particularly by interfering with Fas apoptotic pathway, as demonstrated by higher serum levels of sFas of RA patients after biological treatment. These data suggest that in patients receiving anti-TNF treatment higher levels of sFas may serve to predict remission. Disclosure of Interest: None Declared